Changes of Tangential Traction after Macular Peeling: Correlation between en-face Analysis and Macular Sensitivity. (4th May 2017) - Romano, Mario R.; Cennamo, Gilda; Cesarano, Ida; Cardone, Domenico; Nicoletti, Giuseppe; Mastropasqua, Rodolfo; Cennamo, Giovanni
ABSTRACT: Purpose : To assess the epi- and intra-retinal morphology changes of the tangential tractions following vitreoretinal surgery for epiretinal membranes and to investigate the correlation between the depth of retinal changes and functional macular sensitivity (MS). Methods : This is a prospective cross-sectional interventional study, in which 73 eyes of 73 patients with diagnosis of idiopathic epiretinal membrane (iERM) were evaluated. All patients received complete ophthalmic evaluation, including axial and en-face scanning spectral domain-optical coherence tomography (SD-OCT) analysis and microperimetry. Follow-up examinations were performed preoperatively 1, 3, and 6 months post-vitrectomy for iERM and inner limiting membrane (ILM) peeling. Patients were retrospectively categorized into three groups according to the degree of visual improvement at 6 months postoperatively ("better, " "stable, " "worse"). The main outcome measures were the changes of depth of traction, which is defined as the first layer without visible retinal folds measured with en-face analysis setting the offset on ILM; ganglion cell complex (GCC) thickness; best-corrected visual acuity (BCVA), and MS. Results : The mean reduction of the depth of the first retinal layer free from traction was 70.10 μm (SD 17.78) in the "better" group ( p < 0.001) and 66.56 μm (SD 18.90) in the "stable" group ( p < 0.001). A correlation was found between the preoperative depth of the first retinal layer free from traction and postoperative MS improvement ( R = 0.47; p = 0.034) only in the "better" group. There was no significant difference in the reduction of traction between the "better" and "stable" groups. Conclusion : The study shows a significant correlation between en-face SD-OCT analysis MS. We found that patients that can significantly benefit from the vitrectomy and iERM-ILM peeling are those with preoperative deeper retinal changes and better BCVA and those without intraretinal cysts. In the presence of superficial retinal changes, the patients do not get any significant functional improvement. The main outcome was visual acuity gain. It is not tested whether patients improved in terms of reduction in metamorfopsia or reduction in binocular complaints.